Determining the efficacy of national strategies aimed at addressing the challenges facing health personnel working in rural areas in KwaZulu-Natal, South Africa - Grace Mburu; Gavin George (AOSIS, 2017)
Background: Shortages of Human Resources for Health (HRH) in rural areas are often driven by poor working and living conditions, inadequate salaries and benefits, lack of training and career development opportunities amongst others. The South African government has adopted a human resource strategy for the health sector in 2011 aimed at addressing these challenges. Aim: This study reviews the challenges faced by health personnel against government strategies aimed at attracting and retaining health personnel in these underserved areas. Setting: The study was conducted in six primary health care service sites in the Hlabisa sub-district of Umkhanyakude, located in northern KwaZulu-Natal, South Africa. Methods: The study population comprised 25 health workers including 11 professional nurses, 4 staff nurses and 10 doctors (4 medical doctors, 3 foreign medical doctors and 3 doctors undertaking community service). Qualitative data were collected from semi-structured interviews and analysed using thematic analysis. Results: Government initiatives including the rural allowance, deployment of foreign medical doctors and the presence of health personnel undertaking their community service in rural areas are positively viewed by health personnel working in rural health facilities. However, poor living and working conditions, together with inadequate personal development opportunities, remain unresolved challenges. It is these challenges that will continue to dissuade experienced health personnel from remaining in these underserved areas. Conclusion: South Africa's HRH strategy for the Health Sector 2012/13-2015/16 had highlighted the key challenges raised by respondents and identified strategies aimed at addressing these challenges. Implementation of these strategies is key to improving both living and working conditions, and providing health personnel with opportunities for further development will require inter-ministerial collaboration if the HRH 2030 objectives are to be realised.